METAFISIKA SERAT JATIMURTI - Siswanto, Joko (Jurnal Filsafat "WISDOM", 2010)
AbstractThis article raises â€œSerat Jatimurtiâ€ as a systematic philosophy with a formal object: ontology. This article shows that: first, â€œSerat Jatimurtiâ€ maintains unity of beings autonomous. Individual beings is not it each him, but an elementary unity and binding in unity. Second, metaphysics of â€œSerat Jatimurtiâ€ have jetty at real world, but in multifarious of being there one ground of being as a being, that is Pure Reality was so-called â€œKahanan jatiâ€ (Real Being). Third, the Real Being is a fundamental idea of metaphysics of â€œSerat Jatimurtiâ€. All their metaphysics are instructed and concentrated on the Real Being: there is nothing, only Allah, that is being which is in fact referred as â€˜Kahanan Jatiâ€.Fourth, â€œSerat Jatimurtiâ€ differentiates the existence into fourstrata of being that is â€œgaris, lumah, jirim and kajatenâ€. The four strata of being are ontological structure of entire reality that is one unity and a bundle of relationship. To comprehend it, hence, human should have dimensions of the four strata. Integration of the four dimensions in awareness, hence, human will be able to catch the overall reality. In this case there is attachment between human being and fact, subject-object.Keywords: ontology, beings, Real Being, four strata.